Government Website Performance During the COVID-19 Pandemic: Comparative Study of Yogyakarta and South Sulawesi, Indonesia - Baharuddin, Tawakkal; Qodir, Zuly; Loilatu, Mohammad Jafar (Journal of Governance and Public Policy, 2022)
This paper analyzes government websites and social media accounts during the COVID-19 pandemic. In a crisis, the government must provide real-time information to store and share information using websites and social media. This paper also compares government websites and social media during the COVID-19 pandemic. This study used a qualitative analysis method with NVivo 12 Plus and Similar-web as analytical tools to assist in capturing data and mining data from government-owned websites and social media accounts. This study’s results explained that local governments' use and availability of websites and social media was the government's response to ensure that access and public information services could run well during a crisis. The performance of government websites was influenced by the intensity of relationships on social networks, such as social media. The higher the engagement of government websites with social media, the higher the level of information dissemination in the community. The findings of this study also indicated that the performance of government websites greatly influenced public trust. The limitation of this research lies in the research method, which only took data for a certain period. Hence, this research still requires further development by using observation or interviews.